Parenting in contemporary Europe a positive approach (Council of Europe Publ., 2007)
This publication is an element of the Council of Europe's recent work in the field of positive parenting leading up to the Committee of Ministers' Recommendation Rec(2006)19 on policy to support positive parenting. The authors review and analyze the major changes affecting parenting in Europe, arising from legal situations, research and practice. This work addresses the core issues related to positive parenting and non-violent upbringing, with particular emphasis on parents' entitlement to support from the state in carrying out their parental tasks. Five themes are focused upon: the legal situation and the results of research: what it means to be a parent according to the United Nations Convention on the Rights of the Child, the Council of Europe and new scientific knowledge; current thinking on the use of violence and corporal punishment against children; responses to family policy, especially in terms of support programs and services for parenting and families; the particular problems and needs of parents and children in situations of social exclusion; and the relationship between parenting and drug-related behavior among children and teenagers. The book also includes the text of the Recommendation Rec(2006)19, "Keys for parents" and "Guidelines for professionals".--Publisher's description.